Impact of Chloroquine Resistance on Malaria Mortality - (:unkn) unknown (My University, 1998)
Over 12 years, from 1984 to 1995, we conducted a prospective study of overall and malaria specific mortality among three rural populations in the Sahel, savanna and forest areas of Senegal. The emergence of chloroquine resistance has been associated with a dramatic increase in malaria mortality in each of the studied populations. After the emergence of chloroquine resistance, the risk of malaria death among children 0–9 years old in the three populations was multiplied by 2.1, 2.5 and 5.5, respectively. This is the first study to document malaria mortality at the community level in Africa before and after the emergence of chloroquine resistance. Findings suggest that the spread of chloroquine resistance has had a dramatic impact on the level of malaria mortality in most epidemiological contexts in tropical Africa.
Keywords: African Research